PET/CT in Hodgkin's Lymphoma - Kayani, Irfan (Springer International Publishing : Imprint: Springer, 2017)
This book is a pocket guide to the practice of PET/CT imaging of Hodgkin's lymphoma. The role of PET/CT in Hodgkin's lymphoma, the characteristic findings and patterns, and the advantages and limitations of this hybrid modality are all clearly described. In addition, information is provided on clinical presentation, diagnosis, staging, pathology, management, and conventional radiological imaging. A useful pictorial atlas is included at the end of the book. PET/CT in Hodgkin's Lymphoma is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, which is aimed at referring clinicians, nuclear medicine/radiology physicians, radiographers/technologists, and nurses who routinely work in nuclear medicine and participate in multidisciplinary meetings. Compiled under the auspices of the British Nuclear Medicine Society, the series is the joint work of many colleagues and professionals worldwide who share a common vision and purpose in promoting and supporting nuclear medicine as an important imaging specialty for the diagnosis and management of oncological and non-oncological conditions.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books